PEMANFAATAN ALAT PERAGA SISTEM PENCERNAAN DALAM PEMBELAJARAN IPA PADA SISWA KELAS V SEKOLAH DASAR - Intan Sukma Wardani; Suwignyo, Muhammad; Destiana, Maya; Aulia, Zahratul (TUNAS : Jurnal Pendidikan Biologi, 2026)
This research was conducted to address elementary school students’ understanding of the human digestive system, which cannot be directly observed. This study aims to investigate the use of digestive system teaching aids as instructional media in science learning for grade 5 students. This research employed a qualitative descriptive method supported by a review study method. The data were obtained from secondary sources based on books, scholarly journals, and related articles. Data were collected using documentation techniques, while analysis of the data was performed using content analysis, including data condensation, data presentation, and drawing conclusions. The data were validated through source triangulation. The results indicate that teaching aids contribute positively to students’ conceptual understanding as well as their activeness, interest, and learning motivation. Therefore, digestive system teaching aids can be considered effective in supporting the science learning process in elementary schools and improving students’ learning outcomes.